2008
DOI: 10.1107/s0907444908004319
|View full text |Cite
|
Sign up to set email alerts
|

Iterative-build OMIT maps: map improvement by iterative model building and refinement without model bias

Abstract: A procedure for carrying out iterative model building, density modification and refinement is presented in which the density in an OMIT region is essentially unbiased by an atomic model. Density from a set of overlapping OMIT regions can be combined to create a composite 'iterative-build' OMIT map that is everywhere unbiased by an atomic model but also everywhere benefiting from the model-based information present elsewhere in the unit cell. The procedure may have applications in the validation of specific fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
128
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(129 citation statements)
references
References 34 publications
1
128
0
Order By: Relevance
“…Locally, electron density maps for the ligands in the cavity were unambiguous as early as unrefined initial F o − F c maps. Final 2mF o − DF c composite omit maps (46) show unbiased electron density for the binding-site ligand and water molecules (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Locally, electron density maps for the ligands in the cavity were unambiguous as early as unrefined initial F o − F c maps. Final 2mF o − DF c composite omit maps (46) show unbiased electron density for the binding-site ligand and water molecules (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…All residues were in the allowed regions of the Ramachandran plot. Crystal structures were confirmed, and potential model bias was removed from the molecular-replacement solutions by building models into a series of iterative build omit maps (59).…”
Section: Methodsmentioning
confidence: 99%
“…Restraints were applied to the DNA to preserve hydrogen bonding within base pairs (NOE), to maintain purine and pyrimidine base planes (planarity) and to fix deoxyribose rings in the C2′-endo conformation (dihedral). Composite omit maps were calculated by systematic exclusion of 5% of the map sections coupled with simulated annealing of the model (300 K initial, −50 K steps) (40). These maps showed that the DNA is B-form and its sequence is distinct throughout.…”
Section: Methodsmentioning
confidence: 99%